Clozapine Use in Patients with Early-Stage Schizophrenia in a Chinese Psychiatric Hospital - Yi, Wenying (Neuropsychiatr Dis Treat, 2020)
OBJECTIVE: Previous studies suggest that clozapine is commonly underutilized and that its initiation is delayed in patients with first-episode schizophrenia. Knowledge regarding clozapine use among Chinese patients with early-stage schizophrenia is limited. The aim of the present study was to investigate the point prevalence of and patterns and factors associated with clozapine use in patients with early-stage schizophrenia discharged from a psychiatric hospital in China. METHODS: A retrospective study was conducted to analyze the prescriptions of 867 consecutive patients with early-stage schizophrenia who were admitted to the Affiliated Brain Hospital of Guangzhou Medical University between Jan 1, 2011 and Dec 31, 2016. RESULTS: At discharge from the hospital, 114 (13.1%) patients were prescribed clozapine. Among the patients taking clozapine, 93 patients (81.6%) were prescribed clozapine polypharmacy, and only 21 patients (18.4%) were prescribed clozapine monotherapy. None of the patients were prescribed an overdose of clozapine. The mean daily dosage of clozapine was 160.97 mg, 149.05 mg and 213.69 mg among all patients taking clozapine, patients taking clozapine polypharmacy and patients taking clozapine monotherapy, respectively. The antipsychotic most frequently combined with clozapine was risperidone. Logistic regression suggested that the length of hospital stay, high school education, lower benzodiazepine use and antipsychotic polypharmacy were independently and significantly associated with clozapine use (P<0.05). CONCLUSION: Although clozapine has been commonly used in China in recent years, the present study found that clozapine was not commonly used in patients with early-stage schizophrenia. An underutilization and delayed initiation of clozapine may exist in a portion of patients with early-stage schizophrenia. Given the unfavorable outcomes of underutilized and delayed clozapine use, future studies may be needed to assess and increase clozapine use in this population.